2020
DOI: 10.37256/fse.122020463
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Postharvest Shelf Life and Quality of Lemon Treated with Different Coatings during Storage

Abstract: The effect of edible coatings such as mustard, olive and soybean oils with 1.5% (w/v) sodium alginate (C6H7NaO6)n on the postharvest shelf life and the quality of Jara Lebu (Citrus medica) in 1.5% perforated LDP (low density polythene) bags at 30-32°C and 80-85% relative humidity were evaluated. The changes of physico-chemical attributes like percent weight loss, percent juice yield, pH, Total Soluble Solids (TSS), percent fruit decay, acidity and vitamin C were observed for 18 days of storage. After observing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 18 publications
1
0
0
Order By: Relevance
“…The current results agreed with previous research that reported a slow decline in TA content in citrus fruits treated with composite coatings [15,36]. Biobased oil-coated fruits possibly delayed the use of organic acid as a source of energy and respiration, thereby retaining the acidity percentage better than the control [37]. Similarly, incorporating orange peel oils in the pectin-based composite coating maintained TA content better than the control [38].…”
Section: Total Soluble Solidssupporting
confidence: 91%
“…The current results agreed with previous research that reported a slow decline in TA content in citrus fruits treated with composite coatings [15,36]. Biobased oil-coated fruits possibly delayed the use of organic acid as a source of energy and respiration, thereby retaining the acidity percentage better than the control [37]. Similarly, incorporating orange peel oils in the pectin-based composite coating maintained TA content better than the control [38].…”
Section: Total Soluble Solidssupporting
confidence: 91%